Exploring benzylic gem-C(sp3)–boron–silicon and boron–tin centers as a synthetic platform. Issue 31 (14th July 2021) - Chen, Wei W.; Fernández, Nahiane Pipaon; Baranda, Marta Díaz; Cunillera, Anton; Rodríguez, Laura G.; Shafir, Alexandr; Cuenca, Ana B.
Abstract : This work explores divergent reactivity of the benzylic gem -boron–silicon and boron–tin double nucleophiles, including the arylation of the C–B bond with Ar–Cl, along with a complementary oxidative λ 3 -iodane-guided arylation of the C–Si/Sn moiety. Abstract : A stepwise build-up of multi-substituted Csp 3 carbon centers is an attractive, conceptually simple, but often synthetically challenging type of disconnection. To this end, this report describes how gem -α, α-dimetalloid-substituted benzylic reagents bearing boron/silicon or boron/tin substituent sets are an excellent stepping stone towards diverse substitution patterns. These gem -dimetalloids were readily accessed, either by known carbenoid insertion into C–B bonds or by the newly developed scalable deprotonation/metallation approach. Highly chemoselective transformations of either the C–Si (or C–Sn) or the C–B bonds in the newly formed gem -Csp 3 centers have been achieved through a set of approaches, with a particular focus on exploiting the synthetically versatile polarity reversal in organometalloids by λ 3 -aryliodanes. Of particular note is the metal-free arylation of the C–Si (or C–Sn) bonds in such gem -dimetalloids via the iodane-guided C–H coupling approach. DFT calculations show that this transfer of the (α-Bpin)benzyl group proceeds via unusual [5, 5]-sigmatropic rearrangement and is driven by the high-energy iodine(iii ) center. As a complementary tool, the gem -dimetalloid C–B bond is shown to undergo a potent and chemoselective Suzuki–Miyaura arylation with diverse Ar–Cl, thanks to the development of the reactive gem -α, α-silyl/BF3 K building blocks.